THE METHOD STUDYING SECONDARY SCHOOL TEACHERS’ PERSONAL SELF-DEVELOPMENT - Schicker, Larisa (PSYCHOLOGICAL JOURNAL, 2020)
The article describes methodological tools assessing secondary school teachers’ personal self-development. The importance of the problem of teachers’ personal self-development is substantiated. The essence of the teacher’s personal self-development is defined; this is a process revealing teachers’ internal potential to improve their personal characteristics and effectiveness of their professional work. The components (cognitive-reflective, value-motivational, operational-activity) of teachers’ personal self-development are presented, as well as dynamic indicators (ontogenetic reflection, general and special knowledge, self-understanding, the value of self-development, the desire for self-actualization, professional motivation, primary actual abilities, self-fulfilment, organizational and communicative skills, secondary actual abilities) assessing a process and end results of teachers’ personal self-development. The high, medium, and low levels of teacher’s personal self-development are described. Teachers with high personal self-development realize and accept previous experience; create their own life; have developed reflectivity; fulfil actively their needs for self-development; accept the reality; respect themselves and others; are independent; are able to self-observation, self-organization, self-control; are able to resolve conflicts. Teachers with average personal self-development remember previous negative experiences; are afraid of changes; their need for their self-development is not formed enough; they form their own judgments about life with the help of others; they are not really independent; their work efficiency is not high; they analyze their own activities poorly; they are not inclined to self-organization; they resolve conflicts with the help of outsiders. Teachers with low personal self-development do not analyze past experience at all; their need for self-development is suspended, depending on the social environment; they do not have the skills for self-organization; they do not able to resolve conflicts. The set of diagnostic techniques for studying the indicators of teachers’ personal self-development is streamlined and the feasibility of it use as criteria is substantiated.